Malaria serology data from the Guiana shield: first insight in IgG antibody responses to Plasmodium falciparum, Plasmodium vivax and Plasmodium malariae antigens in Suriname - Mergiory Y. Labadie-Bracho; Farah T. van Genderen; Malti R. Adhin (Malaria Journal, 2020)
Abstract Background Suriname has accomplished a steep decline in malaria burden, even reaching elimination levels. Plasmodium serology data are not available for Suriname and even extremely scarce within the region, therefore malaria serology testing was introduced, country customized cut-off values were determined and a study was performed to explore the antibody status for Plasmodium falciparum, Plasmodium vivax and Plasmodium malariae. Methods A cross-sectional survey was conducted between July 2017 and March 2018 in two areas of the interior with different malaria settings: Stoelmanseiland, representing Maroon villages and Benzdorp, a gold mining area, with mostly Brazilian miners. Dried blood spots (DBS) were collected (n = 197) and antibody presence against seven Plasmodium antigens was detected using a multiplex bead-based, IgG antibody assay. Demographic information was gathered through a questionnaire. Country customized cut-off values were generated from a Surinamese malaria-naïve reference population (n = 50). Results Serological analysis for the reference population revealed cut-off values ranging from 14 MFI for LSA-1 to 177 MFI for PmMSP-119. Seroprevalence against any of the three MSP-119 antibodies was similar in both regions and surpassed 75%. Single seropositivity against PfMSP-119 antibodies was higher in Stoelmanseiland (27.0%) than Benzdorp (9.3%), in line with the historical malaria burden of Stoelmanseiland, while the reverse was observed for PvMSP-119 antibodies. Despite sporadic reports of P. malariae infections, PmMSP-119 antibody presence was 39.6%. A more detailed examination of P. falciparum serology data displayed a higher seroprevalence in villagers (90.7%) than in Brazilians (64.6%) and a highly diverse antigenic response with 22 distinct antibody combinations. Conclusions The results on the malaria antibody signature of Maroon villagers and Brazilian miners living in Suriname displayed a high Plasmodium seroprevalence, especially for P. falciparum in villagers, still reflecting the historical malaria burden. The seroprevalence data for both regions and the observed combinations of P. falciparum antibodies provided a valuable dataset from a historically important region to the international malaria serology knowledge. First insight in malaria serology data for Suriname indicated that the use of other target groups and assessment of age-dependent seroprevalence are required to successfully use malaria serology as tool in the national elimination strategy.